Survival Analysis Of Long Time To Recovery Of Covid-19 Patients Using The Antiviruses Remdesivir And Favipiravir Using The Kaplan-Meier Method - Agung Prabowo; Diniatul Akmalina; Assana Dea Siahaan; Flower of Your Dreams Yati Puty (Research Collaboration Community (RCC), 2025)
The coronavirus first appeared in Wuhan, China, in early December 2019. This virus is also known as Coronavirus disease 2019 (COVID-19). Based on the increasing number of COVID-19 cases and the high number of deaths, further research is deemed necessary. In this case, an effective treatment is needed to accelerate patient recovery. Two commonly used drugs are Remdesivir and Favipiravir. This study used the Kaplan-Meier method to evaluate the recovery time of COVID-19 patients based on two types of treatment: Remdesivir and Favipiravir. Survival analysis was conducted to compare the effectiveness of the two treatments in prolonging patient recovery time. The results showed a difference in effectiveness between the two types of treatment in terms of survival probability.